Atalho (Geograficidade, 2024)
The current experimentation, grounded in a poetic approach, delves into the familiar urban space through a phenomenological lens, emphasizing the experiential interaction with the geographical environment. This reflection challenges dogmatic and orthodox views, rethinking diverse ways of perceiving and feeling the world, as well as its interconnections and dialogues with Geography and the construction of scientific knowledge. This poetic reverie, with a humanistic and cultural focus, alternatively challenges established paradigms and encourages a geographical understanding from a distinct perspective, even in familiar contexts. The poetry, by evoking through the unknown in the seemingly known, aligns with the principles of experience, exploring the connections of the subject with space and proposing a continuous redefinition of our own relationship with the world.